(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Between the Assassinations written by Adiga outlines India between major historical conflicts. The novel mirrors the issues pertaining in the society on the basis of religious.political and economic status. The consequences of discriminations faced by the protagonist of all the stories are painted explicitly by Aravind Adiga. Child labour, corruption, haves and have nots divide, caste, economic inequality, poverty, bribe are revealed as the blatant truth of the society in India. The real picture of dalits through the story of Xerox Ramakrishna is assayed realistically. Religious fanaticism is delved in an explicit manner. The paper attempts to throw lights on India in darkness through Between the Assassinations